Collaboration Of Penta Helix Model Towards The Smart City Program In South Bangka Regency - Dicky Amrullah; Harits Hijrah Wicaksana; Agung Edi Rustanto; Hidayat Sutawijaya; Valentina Moiso; Micaela Mazzei (LPPM Universitas PGRI Sumatera Barat, 2024)
As a form of local government commitment in supporting the national development agenda towards a smart city, the South Bangka Regency Government is accelerating development by implementing a design for the use of information technology for the development of South Bangka as a smart city. This study applies the penta helix collaboration model in the smart city program in South Bangka Regency. The penta helix model involves five main elements, namely government, community, private sector/business actors, academics, and mass media. This study aims to analyze the direction of smart city policy in South Bangka Regency and analyze the penta helix collaboration model in the smart city program in South Bangka Regency. This research method uses a descriptive qualitative approach by conducting in-depth interviews, field observations, and documentation studies with informants. The results of the study indicate that effective collaboration between elements of the penta helix model can increase efficiency, improve public services, and improve community welfare. However, the conclusions of this study also identify a number of challenges, such as lack of coordination between sectors and limited resources. Recommendations put forward include strengthening the regulatory framework, strengthening stakeholder coordination, and increasing human resource capacity, as well as developing information technology infrastructure. This study is expected to contribute to the literature on the implementation of smart cities in other regions with similar characteristics.